Results of Questionnaire Survey among Selected Tourism Enterprises and Their Reflection on Trends in Tourism in the Moravian-Silesian Region - KAJZAR, Patrik; KOSTKOVÁ, Miroslava; PELLEŠOVÁ, Pavlína (Journal of Environmental Management and Tourism, 2020)
The article deals with the entrepreneurs providing tourist services especially in tour operators (TO) and travel agencies (TA) in the Moravian-Silesian Region. The topic of trends in tourism is an up-to-date topic not only from the scientific but also in practical terms. On the basis of the survey, the objectives of the research are to identify selected tourism trends in the offer of TO/TA influencing their activities in the tourism market in the Moravian-Silesian Region. One of the main research questions was to explore whether professional behavior and corresponding ratio of price/quality belong to significant factors influencing purchasing a tour from TO/TA offer. The primary data was acquired from the selected tourism subjects, with the focus of the research and was analyzed using SPSS software. According to the survey are significant factors influencing purchasing a tour from TO/TA offer service from the perspective of the TO/TA next to the offer knowledge and ability to provide as much information as possible, belongs to professional behavior and corresponding ratio of price/quality and TO/TA are focused on searching new experiences, sightseeing tourism, senior tourism, active and adventure trips, discovering unique places, youth tourism, etc.